Budgeting technology as a tool of enterprise management - Zamoroka, M.; Bozhok, Natalia (My University, 2014)
In the article the approaches to the term «budget» are analyzed from the point of view of home and foreign scientists. The main components of the mentioned term, its role and functions in enterprise management are determined.
Keywords: бюджет; підприємство; управління; budget; enterprise; management; кафедра ділової іноземної мови та міжнародної комунікації